Penerapan Algoritma Backpropagation Pada Game Pengenalan Nahwu Di Mi Darul Falah Jepara - Kusumodestoni, R Hadapiningradja; Sucipto, Adi; Ismiati, Sela Nur; Abid, M Novailul (P3M Politeknik Negeri Banjarmasin, 2019)
Nahwu is a science that studies Arabic grammar. Nevertheless, the interest of students in learning nahwu is currently decreasing. It happens because the technological advancement vastly develops but the way of learning it is still conventional and tends to be boring. Based on the school data for the academic year of 2017/2018 at MI Darul Falah Sirahan Cluwak Pati, there were only 20 students able to undestand nahwu well out of 60 students who started learning nahwu in class IV. Technological development has brought many changes to things around us. One of the most developed at the meantime is game. Lately games have become something very fast developing. Using the game to be used as a secondary learning media for students in learning nahwu is considered quite effective. The method used in designing this game was Backpropagation meaning an algorithm based on artificial neural networks which is used to determine and take decision that is used to determine scores and levels in the Nahwu Introduction Game. The tools used in this game-making are construct 2, an HTML5-based game maker specifically for the 2d platform. The results of this study were an Android-based Nahwu Introduction Game.